DETERMINAN KEPATUHAN WAJIB PAJAK (Studi pada Wajib Pajak Orang Pribadi di KPP Pratama Semarang Selatan) - Villa Puspitasari Indah Pertiwi, 12.05.52.0024; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the influence of the level of understanding, taxation awareness, tax sanctions, fiscal services, and modernization of tax administration system to the taxpayer compliance of individuals in the area of KPP Pratama Semarang Selatan. The population in this study is an individual taxpayer in the area of KPP Pratama South Semarang. Sampling was done by convenience sampling technique. The number of samples determined as many as 63 respondents from the number of individual taxpayers registered in KPP Pratama Semarang Selatan. Data analysis technique used in this research is multiple regression analysis technique. The results of this study can be concluded that the level of Understanding has a positive effect on taxpayer compliance. Tax awareness has a positive effect on taxpayer compliance. Tax sanctions have a positive effect on taxpayer compliance. Fiscal services have a positive effect on taxpayer compliance. Modernization of the tax administration system has a positive effect on taxpayer compliance.Keywords:Â Taxpayer Compliance, Level of Understanding, Taxation Awareness, Taxation Sanction, Fiscal Services, and Modernization of Tax Administration System